Purification and characterization of an extracellular protease from Pseudomonas cepacia. - McKevitt, A I (1989)
An extracellular proteinase (PSCP) produced by Pseudomonas cepacia was purified from culture supernatants by ammonium sulfate precipitation, anion exchange chromatography on DEAE-Sephacel, and G200 gel filtration chromatography. The protease has an apparent Mr of 34,000 by electrophoresis. Substrates cleaved by the protease include gelatin, hide powder, and collagen but not human immunoglobulin G (IgG), IgM, secretory IgA, or IgA. The enzyme had the characteristics of a metalloprotease, a pH optimum of 6, and a temperature optimum of 45 degrees C. Intratracheal instillation of purified PSCP into rat lungs produced a bronchopneumonia characterized by polymorphonuclear cell infiltration and proteinaceous exudation into large airways. Rats responded immunologically to active immunization with PSCP, but this response was not protective against subsequent lung infection with P. cepacia. PSCP was shown to have antigenic similarity with Pseudomonas aeruginosa elastase by an immunoblotting technique. Sera from 10 cystic fibrosis patients, with and without a previous history of P. cepacia colonization, were shown to possess antibody reactive against PSCP.